Ostracoda of Fat’ha Formation (Middle Miocene) from (Darbandikhan and Aghjalar) sections, Sulaimani- Kurdistan Region/ Northeastern Iraq - Hawramy, Omran Abdulla; Khalaf, Saleh Khuder (Sulaimani Journal for Pure and Applied Sciences, 2013)
The present study investigated Middle Miocene Ostracoda from the two outcrops of Fat’ha Formation (M.Miocene), Sulaimani area, Kurdistan region NE Iraq. Twenty six Ostracod species belongs to twenty genera recorded in the present study in addition to new two morphotypes. On the basis of the stratigraphic distribution of the Ostracode species recorded in the present study, three Ostracode Assemblage Biozones were proposed in Darbandikhan section, and two Ostracode Assemblage Biozones in the Aghjalar section. Correlation based on the geographical distribution of the recorded genera with India, Iran, Turkey, North Africa and South Europe, in order to identify the Bioprovinces during the Miocene and the nature of marine connections. Based on the Ostracoda genera and the sedimentary evidence, the environment of the Fat’ha Formation interpreted in the studied area.